An Incidental and Parodic Globe. About the Canonical Icon in Cover-Globalization - Davila Legerén, Andrés (CIC. Cuadernos de Información y Comunicación, 2007)
The allegorical proliferation of the globe on the covers of those books dedicated to the analysis and discussion of the present globalization process, homologates the many different ways it should be looked. Our incidental regard meets once and again with this raised iconogram like a canonical icon of globality and nevertheless we hardly are engaged in its power of infographical charm. In these pages we make a slight checking of those iconographical configurations, pointing some parodical traits.